2009
DOI: 10.1111/j.1439-0434.2008.01475.x
|View full text |Cite
|
Sign up to set email alerts
|

Host Specificity and Genetic Diversity of Didymella bryoniae from Cucurbitaceae in Brazil

Abstract: Thirty-seven isolates of Didymella bryoniae from three Cucurbitaceae species were collected in Brazil and tested for pathogenicity to watermelon. All isolates were pathogenic but differed in aggressiveness levels. Seven representative isolates were used in cross-pathogenicity tests against 10 cucurbitaceous hosts. Most isolates were pathogenic to most host species tested, except to Sechium edule. Among the susceptible species, Citrullus and Cucumis species were the most susceptible hosts, while pumpkin and Luf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Some authors have reported the influence of environmental conditions and differences in the aggressiveness of isolates (Santos et al, 2009b;2013).…”
Section: Validation Of Melon Genotype Resistance To D Bryoniaementioning
confidence: 99%
“…Some authors have reported the influence of environmental conditions and differences in the aggressiveness of isolates (Santos et al, 2009b;2013).…”
Section: Validation Of Melon Genotype Resistance To D Bryoniaementioning
confidence: 99%
“…In this period, the watermelon plants subjected to organic management showed higher AUDPC while the other treatments were statistically equal (Tukey test, P<0.05). The presence of rains, resulting in increased relative humidity, creates an ideal microclimate for emergence of fungal diseases, such as gummy stem blight (D. bryoniae) in watermelon and melon and black-sigatoka (Mycosphaerella fijiensis) in banana microclimate (UCHÔA et al, 2012;SANTOS et al, 2013). Moisture is essential for germination and germ tube penetration of most fungal spores by natural and/or injury of leaves and branches (SANTOS et al, 2013).…”
Section: Augmentioning
confidence: 99%
“…The cultivation of watermelon is easy to handle and with lower production costs compared to other vegetable crops. The incidence of diseases is considered one of the limiting factors to the production of watermelon, in view of the huge losses in productivity and fruit quality (SANTOS et al, 2013). Moreover, the incidence of diseases affects fruit appearance leading to its disposal and therefore increased cost of production (MIRANDA et al, 2005;LEÃO et al, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations